The Establishment of Institutional Diagnostic Reference Levels (DRLs) in the Cipto Mangunkusumo Hospital - T. Amalia; B. Zulkarnaien; C. Anam; K. Nurcahyo; H. Tussyadiah; D. E. Pradana (PPIKSN-BATAN, 2022)
Institutional diagnostic reference levels are used for quality assurance in radiology departments. The purpose of this study was to establish an institutional diagnostic reference level (DRL) and to provide a practical tool in diagnostic radiology and nuclear medicine. For each type of procedure/examination, it needs at least 20 patients. The patients with regular size (average body size is 65 ± 10 kg for adult patients and 15±15 kg for pediatric patients) were enrolled in this project. The 75 percentile values of doses were used as institutional DRLs. For nuclear medicine, the administered activities was based on the dose of activity to produce a good image. The DRL values were obtained for general radiography, nuclear medicine, mammography, CT examination, and interventional radiography. The DRL's result was compared to national DRL (NDRL) and values in other countries. The DRL values for general radiography in this study are higher compared to NDRL and Japanese study. The administered activities (MBq) for nuclear medicine in this study are higher compared to European Commission but lower when compared to a Japanese study. The DRL values for mammography in this study are higher compared to ARPANSA; however, they are lower than NDRL and UK studies. The DRL values for CT examination in this study are higher compared to Netherland, Canadian, and USA studies but lower than NDRL. The DRL values in interventional radiography (IR) in this study are lower compared to the IAEA study. This finding indicates that it is still necessary to optimize procedures in the future. The established institutional DRL values can be used as a tool for optimization.